Inversion of winter wheat canopy chlorophyll content using angle-insensitive UAV-based spectral indices - Ye, Sumeng; Zhang, Zhitao; Chen, Junying; Chen, Haiying; Zhang, Bei; Bai, Xuqian; Yang, Ning; Du, Ruiqi; Yang, Xiaofei; Xu, Qi; Qian, Long; Chen, Yinwen; et al. (Computers and electronics in agriculture, 2025)
•Two-band spectral indices, which has higher accuracy and stability in multi-angle estimation of CCC.•The angle at hotspot demonstrated the highest accuracy for CCC estimation.•The PSO-BP algorithm has better results in the multi-angle study of monitoring CCC. Canopy chlorophyll content (CCC) is a vital indicator of crop growth. Timely, efficient and non-destructive estimation of CCC is crucial for field management. However, current methods for constructing CCC inversion models based on orthophoto information face challenges, such as limited accuracy and inadequate information retrieval. To address these problems, this study adopted multi-angle image information. During the main growth period of winter wheat (February to May), CCC measurements and high-resolution multi-angle multispectral remote sensing images were collected. The angle-insensitive spectral indices were screened by correlation and deviation analysis. Using these spectral indices and measured CCC date, four CCC estimation models were constructed: Partial Least Squares Regression (PLSR), Random Forest (RF), Extreme Gradient Boosting (XG-BOOST) and Particle Swarm Optimization-Backpropagation Neural Network (PSO-BP). The results were as follows: (1) Two-band spectral indices (SI) exhibited a stronger correlation with CCC and higher angle applicability. In particular, the near infrared band was the least affected by angle variations; (2) Among 13 observation angles, the overall performance of the four algorithms were basically consistent: the observation angles at the backward of the Solar Principal Plane (SPP) consistently outperformed others, with the optimal observation angle identified at the hotspot (VAA2-45°); (3) The PSO-BP model demonstrated the best performance and overall stability, achieving the highest accuracy at the optimal angle (R2 = 0.91, RMSE = 0.18 mg/g). These results provide valuable insights into selecting optimal observation angles and constructing CCC estimation models using UAV-based multi-angle multispectral remote sensing images.